Pengaruh Pemanfaatan Bahan Ajar Berbasis Tik dan Bahan Cetak Terhadap Motivasi Belajar pada Mata Pelajaran Aqidah Akhlak di MAN 1 Sinjai - Jamaluddin Jamaluddin; Muhammad Khalifah Mustami; Muhammad Ilyas Ismail; Siti Mania (Edukasi Islami : Jurnal Pendidikan Islam, 2022)
As advances and developments in technology and learning media demand the importance of using ICT-based teaching materials, so does the establishment of printed teaching materials. Generally, these teaching materials have been used in various subjects including Aqidah Akhlak subjects at MAN 1 Sinjai. Therefore, the aim of the study was to determine the significant effect between the use of ICT-based teaching materials and printed materials on learning motivation. This research is an ex post facto quantitative approach. The population in this study was class XI students at MAN 1 Sinjai in 2019/2020 consisting of 9 groups with a total number of 238 students. From the total population, to determine the sample used the Equalsize Cluster Random Sampling technique, the number of samples obtained consisted of class XI religion 24 people, XI MIPA 3 as many as 32 people, and XI IPS 4 totaling 28 so that the sample obtained was 84 people. The method of collecting data is through questionnaires. Data analysis is through inferential statistical analysis using multiple regression. The results of this study indicate that there is a significant effect between the use of ICT-based teaching materials and printed teaching materials together on learning motivation at MAN 1 Sinjai with a percentage of 31.8%.